Issues Faced by Micro Businesses during COVID-19: The Integration of Lean Practices and TRIZ - Azyyati Anuar; Daing Maruak Sadek; Law Kuan Kheng; Mohamad Fazali Ghazali; Mohd Zulfabli Hasan; Nurul Fadly Habidin (Information Management and Business Review, 2023)
This research illustrates the importance of micro-businesses in Malaysia and the country's economy. This is followed by the issues they face during COVID-19, including supply chain disruptions, profit loss and challenges in gaining financial aid, adjusting to online business, and retaining workers’ motivation. To address these obstacles, the use of lean practices and TRIZ (Theory of Inventive Problem Solving) methodologies was suggested. Furthermore, past research on the issues that micro businesses face during COVID-19 and lean practices and TRIZ’s potential to solve these issues are reviewed. Data collection will be conducted through semi-structured interviews, focus groups, observation, and document analysis, followed by data analysis through the thematic analysis method. Based on the qualitative analysis results, a model was suggested to demonstrate the association between the key themes emerging from the data. As the study unfolds, it is expected to unveil how lean practices synergize with TRIZ methodologies, enabling a dynamic and holistic response to the multifaceted challenges posed by the COVID-19 pandemic. By strategically aligning these two potent strategies, the model is poised to illuminate pathways toward enhanced operational efficacy, resilience in the face of supply chain disruptions, creative adaptation to the digital realm, and the nurturing of workforce motivation and engagement. As a conclusion, the integration of lean practices and TRIZ helps Malaysia’s micro businesses enhance their operations and adjust to the issues in the current economic environment after COVID-19